Synthesis and Characterization of New 2-amino-5-chlorobenzothiazole Derivatives Containing Different Types of Heterocyclic as Antifungal Activity - Shaima Ibraheem Chyad AL-Khazraji; Wafa Mohammad Sadik; Luma S. Ahamed (Baghdad Science Journal, 2024)
Nine new compounds of 2-amino-5-chlorobenzothiazole derivatives were synthesized. These new compounds were formed through the reaction of 2-amino-5-chlorobenzothiazole 1 with ethyl chloroacetate and KOH, which gave an ester derivative 2, followed by refluxing compound 2 with hydrazine hydrate to afford hydrazide derivative 3. The reaction of compound 3 with CS2 and KOH gave 1,3,4-oxadiazole-2-thiol derivative 4, and then the reaction of compound 2 with thiosemicarbazide to produce compound 5  then treated it with 4%NaOH led to ring closure to provide 1,2,4-triazole-3-thiol derivative 6. The reaction of 2-amino-5-chlorobenzothiazole1 with chloroacetic acid gave 7 followed by refluxing the latter compound with ortho amino aniline giving benzimidazole derivative 8. Azomethine 9 was synthesized over 2-amino-6-chloro-benzothiazole with bromobenzaldehyde, the last compound 9 was converted to a thiazolidinone derivative 10 through the reaction of compound  9 with 2-mercaptoaceticacid. The prepared derivatives were established by using FT-IR, 1H-NMR spectroscopy, elemental analysis C.H.N. and physical properties. Entirely compounds were examined for their anti-fungal action against Candida glabrata and Aspergillus niger, and the results revealed that some compounds showed a good measurable activity comparing with fluconazole as stander drug.